How Does Guided Inquiry Enhancing Students’ Mathematical Literacy? An Experimental Study for Mathematics Learning - Luthfi Nur Azizah; Ali Mahmudi (Southeast Asian Mathematics Education Journal, 2020)
This paper reports a quasi-experimental study with one group pre-test post-test design on promoting mathematical literacy using guided inquiry method. As one of the important education goals globally, mathematical literacy focuses on a concrete dimension with context and content to be studied. A total of 32 secondary school students of class VIII participated as a sample and 192 students as a population in the study. Students' mathematical literacy was measured by using an essay test. The students' responses were analysed and compared using paired sample t-Test. It was found that the guided inquiry method successfully promotes students' mathematical literacy as indicated by the result of paired sample t-test values of significance (2-tailed) of 0.000 < 0.05. Thus, the guided inquiry can be used as an alternative learning method to improve students' mathematical literacy.